Reversible magnetocaloric effect and critical behaviors in Mn1.9−xCoxSn compounds. (5th December 2018) - Feng, W J; Gao, L; Fan, X L; Li, C M; Wang, S; Hong, X; Sun, X S; Gao, M; Deng, Y F
Abstract: The structure, magnetic properties and magnetocaloric effect in the Mn1.9− x Co x Sn ( x = 0, 0.2, 0.4) compounds have been investigated. The reversible magnetic-entropy changes Δ S m max of Mn1.9 Sn and Mn1.7 Co0.2 Sn are 2.13 (209 K) and 1.08 (113 K) J kg −1 K −1, respectively, for magnetic field change between 0–5 T. The critical exponents in Mn1.9 Sn and Mn1.7 Co0.2 Sn compounds have been determined. In the critical region, the data points of magnetization, field and temperature near T C fall into two universal curves. By analysis on the critical exponents, we thought that the short-range ferri-magnetic order occurs in x = 0 compound at T < T C and in x = 0.2 one at T > T C . T he analysis on long-range attractive interactions J ( r ) reveals the dominant long-range interactions in the vicinity of T C in both compounds, besides a little short-range ferro- or ferri-magnetic order.